Hydrogen Sulfide Removal from Biogas Using Digester Effluent Absorbent in a Continuous Vertical Column - Sunu Herwi Pranolo; Paryanto Paryanto; Margono Margono; Bachtiar Rizaldy; Hendrix Yansah (Dept. of Chemical Engineering, Diponegoro University, 2018)
HYDROGEN SULFIDE REMOVAL FROM BIOGAS USING DIGESTER EFFLUENT ABSORBENT IN A CONTINUOUS VERTICAL COLUMN. Gas-Liquid mass transfer is one of the most commonly used phenomena in the chemical process, such as absorbtion. This research evaluates the value of liquid phase mass transfer coefficient of hydrogen sulfide removal from biogas in a continous contactor column for digester effluent-biogas system. This study was carried out by contacting biogas at certain flow with digester effluent continously in a counter-current flow packed bed column. Samples were taken in steady state condition. This research used raschig rings, large balls, and small balls as packing materials with surface areas are 0.9269 m2/m3, 0.6279 m2/m3, and 0.2992 m2/m3 respectively at volumetric flow rates of biogas from 0.1109 m3/h to 0.8846 m3/h. The results show that the relationship between the variables and mass transfer coefficient gives following mathematical model This model is valid in the range of (As·dt) and (Vg/dt·DL) respectively from 0.03 to 0.09 and from 237,267.08 to 3,307,522.67. Average error is 17.85%.